An Educated Community: The Key To Participatory Election Monitoring - Pamungkas, Alim Harun; Zulkarnain, Zulkarnain; Bustami, Abd. Latif (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This paper was compiled based on literary sources which explain participatory election supervision as a form of active involvement of the community and all components of government and communities outside the Election Supervisory Body in supporting the implementation of election supervision. A participatory society is understood to be born from a society that has awareness. Awareness is driven from a set of knowledge and skills and morals that a person has. The Need for Achievement (n-Ach) approach and social change are used as an analytical tool for literature review. This paper concludes that the active involvement of the community demands a change in the attitude of the bureaucracy and its accompanying institutions. The views of the organizers of election supervision must be based on the idea that society can improve the ongoing process of implementing election supervision provided that they are given the trust and opportunity.